VD_FINDINFO HC / 2011 / 265 vom 13. Mai 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, LOCAL PROFESSIONNEL, RÉSILIATION, EXPULSION DE LOCATAIRE, DÉLAI | 257d CO, 271 CO, 271a CO, 311 CPC (CH), 317 CPC (CH)